Sketsa Dakwah Islam di Eropa Barat - Aliyudin Aliyudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
The history of Dakwah  in West-Eropa  can be devided in two patterns: The first, from century 8th to 15th , named at least as politic dakwah. Muslims have real authority in some areas: a few islands in midle sea and minor place in south-Italia and Franch, nor Spanish and Sicilia. The second, sine 19th century  till now, muslims haven’t political authority. The pattern of dakwah only depend on profile, personality, performance of muslim imigrans  behavior as worker, trader, student, diplomat, ect.